Biochemical characterization of avian influenza viral polymerase containing PA or PB2 subunit from human influenza A virus - TURAN, KADİR (ELSEVIER SCIENCE BV, 2018)
Adaptive mutations in viral polymerase, which is composed of PB1, PB2, and PA, of avian influenza viruses are major genetic determinants of the host range. In this study, to elucidate the molecular mechanism of mammalian adaptation of avian viral polymerase, we performed cell-based vRNP reconstitution assays and biochemical analyses using purified recombinant viral polymerase complexes. We found that avian viral polymerase from A/duck/Pennsylvania/10,218/84 (DkPen) enhances the viral polymerase activity in mammalian cells by replacing the PA or PB2 gene with that from human influenza virus A/WSN/33 (WSN). Chimeric constructs between DkPen PA and WSN PA showed that the N-terminal endonuclease domain of WSN PA was essential for the mammalian adaptation of DkPen viral polymerase. We also found that the cap-snatching activity of purified DkPen viral polymerase was more than 5 times weaker than that of WSN in vitro in a PB2 Glu627-dependent manner. However, the cap-snatching activity of DkPen viral polymerase was hardly increased by replacing DkPen PA to WSN PA. These results suggest that the activity of viral genome replication may be enhanced in the DkPen reassortant containing WSN PA. (C) 2018 Institut Pasteur. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Cap-snatching; Endonuclease; Mammalian adaption; Reassortment; Viral polymerase; ADAPTIVE MUTATIONS; HOST RESTRICTION; RNA-POLYMERASE; INCREASED VIRULENCE; AMINO-ACID; MICE; PROTEIN; ENDONUCLEASE; ADAPTATION; REPLICATION